LOGISTIC TRENDS IN S UPPLY CHAINS (Perner's Contacts, 2018)
The article deals with logistic trends in supply chains. Technical and technological development has a major influence in supply chains. We must not forget the ever-growing importance of globalization. Among the selected trends in supply chains are included in this article robotization, automation, digitization, emphasis on green and lean logistics and the process of integration in supply chains.
Keywords: supply chain, integration, automation, green logistics